C-reactive protein associated with the periodontal condition of pregnant women - Pesantes Sangay, Sandra Jessenia (2020)
Objective: To determine the C-reactive protein level according to the periodontal state, age and trimester of pregnancy in pregnant women who attend the Centro de Salud Magna Vallejo, Cajamarca, Peru. Materials and methods: An observational, descriptive and cross-sectional study conducted in a sample of 60 pregnant women divided into three groups: those who were periodontally healthy, those with gingivitis and those with periodontitis. The Russell Index was used to determine the periodontal status. The value of the C-reactive protein level was taken from each patient’s medical record. Results: An elevated C-reactive protein level was found in 66.70 % of the pregnant women with gingivitis, 100 % of the pregnant women with periodontitis and 84.60 % of the adult pregnant women. Conclusions: C-reactive protein levels tend to rise in patients with periodontal disease and increase in adult pregnant women.